Peningkatan Aktivitas dan Hasil Belajar IPA Materi Pewarisan Sifat Dengan Media Kartu Dogen - Waluya, Tuwuh (LP3 Universitas Negeri Semarang, 2015)
This study aims to improve the learning outcomes of activities and materials science of heredity through the use of media cards for students of classes IX Dogen E SMPN 5 Kudus in the 1st half 2014/2015 Academic Year. The subjects studied are students of class IX E SMPN 5 Holy in the 1st half 2014/2015 Academic Year. Objects are the Class Action Research Dogen card utilization, low activity and results belaja students. The method used in this research is using Action Research (PTK) or Classroom Action Research with two cycles. The steps from planning, implementation, observation through reflection. The analysis technique used comparative descriptive technique, followed by reflection. The results showed that Dogen card media can increase the activity and learning outcomes hereditary material science for students of classes IX E SMPN 5 Holy in the 1st half 2014/2015 Academic Year. This is apparent from the initial conditions of students' learning activeness low to the final conditions of high activeness of student learning. With the use of the media card Dogen in the material science of heredity can improve.